P02.04 Tumor treating fields induce immunogenic cell death resulting in enhanced antitumor efficacy when combined with anti-PD-1 therapy. (19th September 2018) - Voloshin, T; David, S; Porat, Y; Shteingauz, A; Munster, M; Kaynan, N; Giladi, M; Kirson, E; Weinberg, U; Palti, Y
Abstract: Background: Tumor Treating Fields (TTFields) are a clinical anti-neoplastic treatment delivered via noninvasive application of low intensity, intermediate frequency, alternating electric fields. The anti-mitotic effects of TTFields include disruption of the mitotic spindle and abnormal chromosome segregation, which trigger different forms of cell death. We evaluated if TTFields-induced cell death is perceived as immunogenic by the immune system. Material and Methods: Murine Lewis lung carcinoma (LLC), CT-26 colon carcinoma, and ovarian surface epithelial (MOSE) cells were treated with TTFields using the inovitro TM system. Calreticulin (CRT) levels on the surface of treated cells and intracellular ATP levels were evaluated using flow cytometry. High mobility group box 1 (HMGB1) secretion was measured by ELISA assay. ER stress was detected by phosphorylation of the translation initiation factor eIF2α using immunoblot analysis. TTFields-induced upregulation of autophagy was evaluated by immunoblot and immunofluorescence of LC3. Bone marrow derived dendritic cells (DCs) were co-incubated with TTFields treated LLC-1 cells and phagocytosis by DCs and DCs maturation were evaluated by flow cytometry. Mice orthotopically implanted with LLC cells were treated with TTFields, immune checkpoint inhibitor anti-PD-1, or a combination of the two. Tumor volume was monitored and flow cytometry analysis performed to phenotypically characterize infiltrating immune cells. Results: Cancer cells died during TTFields application exhibiting ER stress leading to CRT translocation to the cell surface, and released damage-associated molecular patterns including the chromatin-binding protein HMGB1 and ATP. TTFields promote upregulation of autophagy which may explain ATP depletion following treatment. TTFields-treated cells promote phagocytosis by DCs and DCs maturation under co-culture conditions. In vivo, the combined treatment of lung tumor-bearing mice with TTFields with anti-PD-1, significantly improved therapeutic efficacy compared to TTFields or anti-PD-1 alone. Significant increase in the number of tumor infiltrating immune cells was observed in the TTFields plus anti-PD-1 group. These infiltrating cells, specifically macrophages and DCs, demonstrated upregulation of surface PD-L1 expression. Cytotoxic T-cells isolated from these tumors showed higher levels of IFN-γ production relative to untreated mice. Conclusion: The results suggest that TTFields application induces both ER stress and autophagy, resulting in immunogenic cell death. Combining TTFields with anti-PD-1 may achieve tumor control by further enhancing antitumor immunity.